SCHVVANNOMA İN THREE PATIENTS WITH LOWBACK PAIN - Halil Uçan; Ümit Seçkin; Gülseren Ak (Archives of Rheumatology, 2000)
Spinal schvvannoma is rare, benign tumors arising from the sheath of the spinal nerve roots. Lovv back pain alone or associated radicular pain has been the initial symptom. Today MRI imaging is the most valid early diagnostic technique. Here we report 3 patients vvith lovv back pain, vvhose investigation presented intradural extramedullary tumors of the spine and their postoperative pathologic examination shovved schvvannomas